Optimalisasi Handover Perawat dengan Komunikasi SBAR Berbasis Elektronik - Kartika, Anika; Yetti, Krisna; Afriani, Tuti; Wulandari, Dyah Fitri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to optimize nurse handover with electronic-based SBAR communication. The research method used is a pilot project. The research results show that implementing nurse handovers with electronic-based SBAR communication in the Emergency Room makes the nurse's work system more optimal, which is demonstrated when patient-related information is clearer, structured and more complete, communication becomes more effective, and can increase patient safety, 27 respondents stated 81.5 % already understand what SBAR communication is and 40.7% have attended SBAR communication training, and as many as 77% have the ability to fill in electronic-based handover formats and are able to carry out handovers using electronic-based SBAR Communication. In conclusion, implementing nurse handovers with electronic-based SBAR communication in the Emergency Room makes the nurse's work system more optimal, which is demonstrated by making patient-related information clearer, structured and more complete, communication becomes more effective, and can increase patient safety. Keywords: Electronics, Effective Communication, Handover, SBAR.